Kriteria Seleksi Penentuan Ketahanan Kedelai terhadap Kutu Kebul - Apri Sulistyo (Iptek Tanaman Pangan, 2016)
Whitefly (Bemisia tabaci Genn.) is a leaf-sucking insect and is a major pest on soybean. Nymphs and adults of whitefly are insect stages that cause damage directly or indirectly on the host plant. Chemical control to the pest has not produced satisfactorily results, and even has given a negative impact on the environment, damaging the efficacy of biological agents, and causing resistance to chemical compounds on whitefly. Pest control techniques based on Integrated Pest Management (IPM) is using the resistant varieties. Selection criteria for resistance to pest are needed based on the resistance mechanism and agronomic characteristic of resistant genotypes. Soybean resistant mechanism to whitefly could be through physical antixenosis, such as through the leaf trichomes and leaf thickness. Based on antixenosis mechanism, selection for resistance is done by counting the number of whitefly infestation (eggs, nymphs, pupas, adults) per leaf area. Antibiosis mechanism was selected by observing the life cycle of whitefly, including the duration of the hatching eggs into nymphs, the development of the nymph into pupa, and the adult insect emergence. Selection of resistant soybean based on tolerance mechanisms was done by observing the decrease in grain yield due to whitefly attacks. Soybean breeding to obtain varieties resistant to whiteflies in Indonesia could use the mechanism of tolerance based on leaf damage intensity, as selection criteria.